Potensi Fungi Endofit Daun Sambung Nyawa (Gynura Procumbens) sebagai Alternatif Antibakteri Baru - Muh Danial Fajri; Djulfikri Mewar; Marhamah Marhamah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
The Sambung Nyawa plant (Gynura procumbens) is known to have various benefits, including as an antibacterial. This study aims to identify and evaluate the antibacterial properties of secondary metabolites from endophytic fungi isolated from Sambung Nyawa leaves against Staphylococcus epidermidis and Staphylococcus aureus bacteria. Fungi were isolated and then fermented for 7 days using Nutrient Broth media. Antibacterial activity was evaluated using agar diffusion technique, with zone of inhibition as an indicator of activity. The results showed that IFDSN 2 fungal isolate had the highest zone of inhibition, with a very strong category against S. aureus and strong against S. epidermidis. This finding supports the potential of endophytic fungi as an environmentally friendly natural antibacterial source.